Artificial neural networks approach to the non-linear analysis of rectangular plates - Civalek, Ömer; Ülker, Mehmet (My University, 2004)
The linear and non-linear analysis of rectangular plates has been presented via artificial intelligence techniques and numerical examples are solved by means of the developed program. The back-propagation neural network has been used in the solution. The thickness of plates has been normalized by the use of the fuzzy triangular membership function. The center point moments and deflection have been obtained for the numerical applications. It has been emphasized that the artificial intelligence technique is an alternative method that can be used in structural engineering.
Dikdörtgen Plaklarin Do?rusal Olmayan Analizinde Yapay Sinir A?i Yaklaşimi
Keywords: Artificial intelligence; Backpropagation; Deflection (structures); Fuzzy sets; Membership functions; Neural networks; Nonlinear systems; Structural analysis; Structural design; Fuzzy triangular membership functions; Non-linear analysis; Rectangular plates; Plates (structural components)